Study on the dissolution of β-precipitates in the Zr–1Nb alloy under the influence of Ne ion irradiation. (8th May 2021) - Goel, Lokesh; Mir, Anamul H; Naveen Kumar, N; Satyam, Parlapalli V; Hinks, Jonathan A; Donelly, Stephen E; Tewari, Raghvendra
Abstract: The stability of β-precipitates in the Zr–1Nb alloy has been studied under Ne ion irradiation of energy 250 keV by in situ transmission electron microscope as a function of irradiation dose. The irradiation was carried out up to ∼136 dpa at 573 K. Microstructural investigations have shown that up to ∼38 dpa, precipitates showed an increase in size, and for irradiation doses >38 dpa, the size of the precipitates was noticed to reduce. Post-irradiation energy-dispersive spectrometry of the specimens revealed the Nb concentration throughout the matrix to be ∼0.8–1.5%. Three-dimensional atom probe tomography was also carried out for irradiated specimens to look for the presence of any nanoclusters. However, Nb clustering was not observed in the specimens. It is proposed that the dissolution of the precipitates may be facilitated by an increase in the solubility limit of Nb in Zr caused by irradiation. The solubility limit may increase by the introduction of defects generated by irradiation and by the destabilization of the β-phase. This may result in back-diffusion of Nb atoms to the matrix by radiation-enhanced diffusion to lower the strain produced by the defects, resulting in the dissolution of the precipitates.